Oral health status in children and adolescents with haemophilia. (10th March 2015) - Othman, N. A. A.; Sockalingam, S. N. M. P.; Mahyuddin, A.
Summary This case‐controlled study aimed to evaluate the existing oral health status in children and adolescents with haemophilia. A total of 50 haemophilia patients and 50 matched controls aged seven to 16 years were recruited into the study. Clinical examination was carried out to determine dental caries experience, oral hygiene status and gingival condition in these two groups. Information regarding previous dental history, oral hygiene practices and dietary habits were also obtained. No significant difference was found in mean caries experience in primary and secondary dentitions (P = 0.86 and 0.32) and in Simplified Oral Hygiene Index (OHI‐S, P = 0.20) between both groups. However, a significantly higher proportion of haemophilia patients (24%) had better oral hygiene status as compared to the controls (2%, P = 0.004). Furthermore, there was a significant difference in Modified Gingival Index (MGI, P = 0.02) between the two groups with the study group having less gingival inflammation. A total of 88% (n = 44) of the haemophilia patients were registered and received dental treatment in specialist dental clinics. More than half (56%, n = 28) had frequent dental visits and only one‐third of the haemophilia patients had history of hospitalization due to oral problems. There was no significant difference in oral hygiene practices and dietary habits between both groups. In general, haemophilia children and adolescents in this study had similar caries experience, a significantly better oral hygiene status and gingival health as compared to healthy controls. The main reason for this is the multidisciplinary approach implemented by medical health‐care professionals as primary care provider and the dental team.